2019
DOI: 10.1007/978-3-030-32281-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Inter-fractional Respiratory Motion Modelling from Abdominal Ultrasound: A Feasibility Study

Abstract: Motion management strategies are crucial for radiotherapy of mobile tumours in order to ensure proper target coverage, save organs at risk and prevent interplay effects. We present a feasibility study for an inter-fractional, patient-specific motion model targeted at active beam scanning proton therapy. The model is designed to predict dense lung motion information from 2D abdominal ultrasound images. In a pretreatment phase, simultaneous ultrasound and magnetic resonance imaging are used to build a regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Autoregressive model The autoregressive model used in this study has been described previously (Giger et al 2019) and, therefore, is only briefly summarised here. Let α t ∈ R u describe the vector of the u most dominant principal components of the US image acquired at time t. Furthermore, let α j t denote the jth element of the vector α t .…”
Section: Motion Modellingmentioning
confidence: 99%
“…Autoregressive model The autoregressive model used in this study has been described previously (Giger et al 2019) and, therefore, is only briefly summarised here. Let α t ∈ R u describe the vector of the u most dominant principal components of the US image acquired at time t. Furthermore, let α j t denote the jth element of the vector α t .…”
Section: Motion Modellingmentioning
confidence: 99%
“…That is why registration algorithms with a temporal regularizer have been proposed [19]- [24]. For respiratory motion modeling, learning-based regression models using ultrasound and MR images of different respiratory states have been used to learn respiratory motion patterns [25], [26]. In the computer vision community, temporal video super-resolution and motion compensation are a related research topic [27], [28].…”
Section: A State-of-the-artmentioning
confidence: 99%
“…Due to physical constraints, direct US imaging of lung tissue is not possible. However, with the help of respiratory motion models, motion characteristics extracted from liver US can be used to estimate lung tumour motion (Mostafaei et al 2018) and lung deformation (Giger et al , 2019. While Mostafaei et al 2018 have demonstrated the correlation between diaphragm motion and lung tumour motion in superior-inferior (SI) direction, Giger et al ( , 2019 have inferred dense lung motion information from 2D abdominal US images.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the help of respiratory motion models, motion characteristics extracted from liver US can be used to estimate lung tumour motion (Mostafaei et al 2018) and lung deformation (Giger et al , 2019. While Mostafaei et al 2018 have demonstrated the correlation between diaphragm motion and lung tumour motion in superior-inferior (SI) direction, Giger et al ( , 2019 have inferred dense lung motion information from 2D abdominal US images. Since we aim to investigate respiratory motion and its variabilities in the context of PBS proton treatment, monitoring 1D tumour motion only is not sufficient as motion information of the surrounding tissue needs to be additionally taken into account (Trnková et al 2018, Bertholet et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation